2019
DOI: 10.1515/ijamh-2018-0039
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pediculosis and its related factors among primary school girls in the north of Iran

Abstract: Introduction Head lice infestation is one of the main public health problems worldwide and a sanitary, cultural and economic indicator for communities’ health. This study aims to estimate the prevalence of head lice infestation among female primary school children in selected districts of Mazandaran Province, Iran. Methods In this cross-sectional study, 3033 female school children were recruited using the consensus method. Head lice infestation was defined as visible adult lice, nymph or egg with the naked e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Some studies have shown that the factors affecting HLI include demographic and socioeconomic factors, lifestyle‑related factors, number of people sharing the room (family size), accessibility to soaps/shampoos, sharing of bed, towels/soaps and combs, bathing, not combing hair, hair longitude and condition, going to the hairdresser, low level of family's knowledge about head lice, its transmission, and treatment, school type (Government/private). 1 , 13 , 14 , 15 , 16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that the factors affecting HLI include demographic and socioeconomic factors, lifestyle‑related factors, number of people sharing the room (family size), accessibility to soaps/shampoos, sharing of bed, towels/soaps and combs, bathing, not combing hair, hair longitude and condition, going to the hairdresser, low level of family's knowledge about head lice, its transmission, and treatment, school type (Government/private). 1 , 13 , 14 , 15 , 16…”
Section: Introductionmentioning
confidence: 99%
“…2,[8][9][10][11][12] Some studies have shown that the factors affecting HLI include demographic and socioeconomic factors, lifestyle-related factors, number of people sharing the room (family size), accessibility to soaps/shampoos, sharing of bed, towels/soaps and combs, bathing, not combing hair, hair longitude and condition, going to the hairdresser, low level of family's knowledge about head lice, its transmission, and treatment, school type (Government/private). 1,[13][14][15][16] Due to the prevalence of head lice in schools and adolescent girls, it seems that some factors affecting this health problem are unknown. According to the study by Nezhadali et al, Cognitive and behavioral factors determined 21% of the variance in predictive behaviors of head lice.…”
mentioning
confidence: 99%